2021
DOI: 10.5539/jel.v10n3p55
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Video: The Effectiveness of Learning Math in Higher Education Through Videos and Texts

Abstract: The Text-Based Video (TBV) model is a particular case of the more general Video-Based Learning (VBL) model in which an instructor’s curriculum is fully covered by high-quality videos and texts. The aim of this study is to test the effectiveness of the TBV model by examining and comparing its two main components: Videos and texts. The model is based on the creation of high-quality texts which form the basis for high-quality video clips. It is designed to improve learning in quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Although, there were no significant differences between the learning management system and their effects on Teaching effectiveness or Class grade point average. In contrast, Ghilay (2019) indicated that there are statistically significant differences of LMS activity between " Low activity level" ( e. g. ; uploading files, sending announcements) and "High activity level" (Additional of Low activity level e. g. ; Restriction of resource accessing, monitoring of learners' activity, etc. ) .…”
Section: Discussionmentioning
confidence: 86%
“…Although, there were no significant differences between the learning management system and their effects on Teaching effectiveness or Class grade point average. In contrast, Ghilay (2019) indicated that there are statistically significant differences of LMS activity between " Low activity level" ( e. g. ; uploading files, sending announcements) and "High activity level" (Additional of Low activity level e. g. ; Restriction of resource accessing, monitoring of learners' activity, etc. ) .…”
Section: Discussionmentioning
confidence: 86%
“…IVs contribute to the students' learning progress in different subjects, especially in science. Studies from other researchers prove that videos are combined visual and verbal compositions that give students a complete package of learning experiences reflecting their [33], [34]. Therefore, all of the participants agreed that using IVs materials positively affects their learning experiences in the science subject.…”
Section: "In My Opinion the Positive Are The Images And How It Points...mentioning
confidence: 83%
“…As education continues to evolve in the digital age, the integration of LMS platforms has become instrumental in transforming traditional learning environments into dynamic online spaces. LMS platforms offer educators and students a versatile ecosystem for content delivery, collaboration, and assessment [1,5,31]. These platforms have been lauded for their effectiveness in promoting self-directed learning and expanding access to educational resources [3].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have increasingly explored the integration of gamification elements within LMSs to enhance the learning experience [1,2]. Gamification, the incorporation of game-like mechanics and design into non-game contexts, has demonstrated its potential to motivate learners and encourage active participation [31]. Studies have shown that gamification elements, such as points, badges, and leaderboards, effectively increase student engagement and participation [17,32].…”
Section: A Lms and Gamification In Educational Contextsmentioning
confidence: 99%